Pengaruh Sistem Informasi Sumber Daya Manusia, Pelatihan, dan Disiplin Kerja terhadap Kinerja Karyawan pada PT. Socfin Indonesia (SOCFINDO) Medan - Indha Aprida Sutari; Folooli Laia; Cut Fitri Rostina (Magister Manajemen Universitas Muhammadiyah Sumatera Utara, 2021)
This study aims to examine and analyze the effect of human resource information systems, training, and work discipline on employee performance. Where the method of multiple linear regression analysis and testing the sample of researchers in the study is to use saturated sampling where the employees of the office of PT. Socfin Indonesia (SOCFINDO) Medan as a sample of 90 respondents and 30 respondents as a test of the validity and reliability of PT. Nusantara IV Medan Plantation. Based on the results of hypothesis testing in this study, it shows that the simultaneous human resource information system, training, and work discipline have a positive and significant effect on employee performance. And partially, the variables of human resource information system, and work discipline have a positive and significant effect on employee performance. Meanwhile, the training variable has no and no significant effect on employee performance.